The porosity distribution in the HTTU annular packed bed of spheres - Potgieter, M.C.; du Toit, C.G. (Nuclear engineering and design, 2023)
•Evaluation of the porosity of the HTTU annular packed bed.•Angular and radial variation in porosity for bottom near-wall region characterized.•Standard deviation and skewness of angular at each radial position calculated.•Variation of tangentially averaged porosity in axi-symmetric r-z plane shown.•Average porosity and standard deviation for 20 selected regions presented. In this paper a comprehensive analysis of the porosity of the annular packed bed of the High Temperature Test Unit (HTTU) is presented. The annular packed bed is generated using a Discrete Element Method (DEM) approach. Semi-analytical methods are then used to analyse the porosity. The quality and representativity of the packed bed are established by evaluating the overlaps between spheres and spheres and walls and comparing the axial and radial variations in porosity with available experimental and numerical data. The angular and radial variation of selected sphere layers in the bottom near-wall region was studied revealing how the spheres in the axial layers and radial rings are staggered with respect to each other. The analysis of the radial variation in porosity also included the standard deviation and the skewness of the angular porosity at each radial position. An analysis of the radial porosity of the layers revealed that only first layer next to the bottom is markedly affected by the bottom wall. The interference between the oscillatory porosity variations perpendicular to the inner, outer, and bottom walls of the annular packed bed is demonstrated by the plot of the variation in porosity on an axi-symmetric r-z plane. The annular packed bed is also divided into 20 regions and the average porosity and the standard deviation of the porosity for each region in provided.